Objectives and Key Results (OKRS) and Their Role in Enhancing Employee Performance: A Systematic Literature Review - Cholifah, Mifthachul; Drahen Soeling, Pantius (Journal of Management, 2025)
Employee performance is influenced by training, compensation, and work discipline; however, many organizations face challenges in managing these factors effectively. Objectives and Key Results (OKR) is a performance management methodology that helps set clear and measurable goals, but its implementation often encounters obstacles such as a lack of understanding and resistance to change. This study aims to review existing literature to understand how OKR can enhance employee performance and identify key success factors. The research employs the Systematic Literature Review (SLR) method to analyze the role of OKR in improving employee performance by collecting and filtering literature from various academic sources using strict selection criteria. The analysis is conducted through a thematic approach, the PRISMA method for literature selection, and validity and reliability evaluation by ensuring the credibility of sources and consistency in data analysis processes. The findings indicate that OKR is an effective management tool for enhancing employee and organizational performance, but its success requires careful planning and strong managerial support. The implementation of OKR must be aligned with organizational culture and strategy to ensure optimal outcomes. Further studies are needed to explore the impact of OKR on employee satisfaction and well-being in digital work environments. For successful implementation, companies must provide adequate training and socialization to foster a transparent and collaborative work culture.